2020
DOI: 10.3390/jcm9072235
|View full text |Cite
|
Sign up to set email alerts
|

Injury of the Tibial Nutrient Artery Canal during External Fixation for Lower Extremity Fractures: A Computed Tomography Study

Abstract: The tibial nutrient artery (TNA) is the major diaphyseal artery of the tibia supplying two thirds of the inner osseous cortex. Hence, iatrogenic injury of the TNA endangers the integrity of the tibial blood supply and may compromise fracture healing. The incidence of its injury in the setting of external fixation for lower limb fractures has not been previously investigated. The aim of this study was to evaluate the incidence of TNA injury in the context of external fixation and to characterize the topography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…At present, the commonly used clinical tibial fracture fixation instruments can easily cause damage to intraosseous blood vessels. According to a retrospective study of 105 patients with tibial fractures treated with external fixators by Almansour et al [ 25 ], at least 38% of the patients had damaged tibial nutrient arteries, which may be conservative given that damage to the nutrient arteries itself cannot be detected by computed tomography. This view is also supported by Brinker et al [ 26 ], who reported a similar situation in patients treated with tibial intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the commonly used clinical tibial fracture fixation instruments can easily cause damage to intraosseous blood vessels. According to a retrospective study of 105 patients with tibial fractures treated with external fixators by Almansour et al [ 25 ], at least 38% of the patients had damaged tibial nutrient arteries, which may be conservative given that damage to the nutrient arteries itself cannot be detected by computed tomography. This view is also supported by Brinker et al [ 26 ], who reported a similar situation in patients treated with tibial intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
“…is calls for some insight into the blood supply of diaphysis of the tibia. e major vascularity in the tibial diaphysis is by the tibial nutrient artery (TNA), which is responsible for supplying the inner two-third of the diaphyseal cortex [9]. e extraosseous blood supply of the tibial diaphysis is poor compared with the proximal and distal metaphysic [25].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgical procedures disturb the soft tissue envelop surrounding the fracture, more so in the tibial diaphysis, which has already a precarious extraosseous blood supply [9]. e osteoperiosteal decortication flap technique effectively addresses this issue in the nonunion tibia and ensures an adequate biological environment at the nonunion site.…”
Section: Background Of the Workmentioning
confidence: 99%
“…At present, the commonly used clinical tibial fracture xation instruments can easily cause damage to intraosseous blood vessels. According to a retrospective study of 105 patients with tibial fractures treated with external xators by Almansour et al [19], at least 38% of the patients had damaged tibial nutrient arteries, which may be conservative given that damage to the nutrient arteries itself cannot be detected by computed tomography. This view is also supported by Brinker et al [20], who reported a similar situation in patients treated with tibial intramedullary nailing.…”
Section: Blood Supply To the Tibia And Treatment Of Fracturementioning
confidence: 99%